The Effect of Work Motivation and Work Environment on Employee Performance at PT X - Yulia, Risa Setiani; Lahindah, Laura (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to know and analyze the influence of work motivation and work environment on employee performance at PT X. Using a quantitative approach with multiple linear regression, this research analyzes data obtained from questionnaires distributed to all permanent employees. The results indicate that both work motivation and work environment significantly and positively affect employee performance. High work motivation encourages employees to achieve the established performance targets, while a conducive work environment provides a sense of security, comfort, and challenges for employees to continue developing. The interaction between the two variables also shows significant results, where a good work environment can enhance work motivation, and vice versa. These findings indicate the importance of the company in managing both factors in a balanced manner. Recommendations for PT X include focusing on programs that can enhance work motivation, such as a fair reward system, career development, and participation in decision-making. Additionally, it is essential to create a conducive work environment through facility improvements, effective communication, and a positive work culture. Thus, this research contributes significantly to the company’s understanding of the factors influencing employee performance. By implementing the provided recommendations, it is hoped that PT X can achieve more optimal and sustainable performance.